DETECTION OF CONGENITAL HEART DISEASE BY FETAL ECHOCARDIOGRAPHY: Congenital Heart Disease - ., Dr. Afshan Fayyaz; Majeed, Syed Muhammad Imran; ., Waqar Ahmed (Pakistan Armed Forces Medical Journal, 2013)
Objective: The objective of the study was to determine the sensitivity, specificity, accuracy and predictive value of fetal echocardiography in our set up using postnatal echocardiography as gold standard. Study Design: Validation study. Place and Duration of study: This is an ongoing study in the Radiology department of CMH Rawalpindi and Armed Forces Institute of Cardiology (AFIC) Rawalpindi and the data collected from January 2007 to Jan 2012 is presented. Patients and Methods: Two hundred eighty seven patients reported for fetal echocardiography. Two hundred twenty nine patients were subsequently included in the study. These included patients of all ages who reported to the Radiology department of CMH Rawalpindi for fetal echocardiography. Fetal echo was done on Toshiba Aplio with 3.5 MHz probe having Doppler facility. Post natal evaluation was done by a pediatric cardiologist. Results: There were 207 (90.4%) true negative cases, 15 (6.6%) true positive, 2 (0.9%) false positive and 6 (2.2%) false negative cases. The sensitivity, specificity, positive and negative predictive values were 75%, 99%, 88%, 97% respectively. Conclusion: Fetal echocardiography has high specificity, negative predictive values and accuracy and cases diagnosed as normal can reassure the parents about the normal cardiac status of the fetus.